Paleoanthropological research in Hungary - Éry, Kinga (Acta Biologica Szegediensis, 2000)
This essay offers a brief and selected review of the paleoanthropological research in Hungary by chronologically listed studies in which new trends, methods and observations are to be found. The studies mostly focused on the populations of the Carpathian Basin according to their origin, regional distribution and morpho-taxonomical characteristics with the help of statistical methods. Their way of life and nutrition, their paleopathological, paleodemographical, paleoserological, paleostomatological and paleosociographical features were also investigated. At the end of the review there is a brief report on the current state of the Hungarian anthropological collections, housed in the Anthropological Department of the Hungarian Natural History Museum, the Department of Anthropology, University of Szeged and in different county museums.